Limits and signatures of relativistic spaceflight. (January 2018) - Yurtsever, Ulvi; Wilkinson, Steven
Abstract: While special relativity imposes an absolute speed limit at the speed of light, our Universe is not empty Minkowski spacetime. The constituents that fill the interstellar/intergalactic vacuum, including the cosmic microwave background photons, impose a lower speed limit on any object travelling at relativistic velocities. Scattering of cosmic microwave photons from an ultra-relativistic object may create radiation with a characteristic signature allowing the detection of such objects at large distances. Highlights: Interstellar/intergalactic space is not empty. Constituents include the cosmic microwave background photons. Speed limit lower than that of light for any object at relativistic speeds. Scattering of cosmic microwave photons from ultra-relativistic objects discussed. Characteristic signatures of the radiation produced identified.